2014
DOI: 10.2214/ajr.13.11905
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Lesions at MRI-Guided Breast Biopsy: Frequency and Rate of Underestimation

Abstract: MRI-guided breast biopsy yielded high-risk lesions in 21.5% of cases, and the underestimation rate was 23.2%. No patient or lesion characteristics correlated with underestimation rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 36 publications
5
31
1
3
Order By: Relevance
“…In this study, the upgrade rate from atypical lesions to cancer due to a finding on BSGI was 21.4% (3/14). This is comparable to existing data demonstrating upgrade rates of 20%-23% for MRI-detected atypia (33,34). These findings suggest that surgical excision should be recommended for all atypical, highrisk lesions found on BSGI.…”
Section: Treatment and Outcome Of Atypical High-risk Lesionssupporting
confidence: 85%
“…In this study, the upgrade rate from atypical lesions to cancer due to a finding on BSGI was 21.4% (3/14). This is comparable to existing data demonstrating upgrade rates of 20%-23% for MRI-detected atypia (33,34). These findings suggest that surgical excision should be recommended for all atypical, highrisk lesions found on BSGI.…”
Section: Treatment and Outcome Of Atypical High-risk Lesionssupporting
confidence: 85%
“…Even with complete removal of malignant microcalcifications by VAB, underestimation rates up to 17 % are documented [2629]. The highest underestimation rates (22–65 %) are published for ultrasound-guided 14G CNB [21, 22, 25, 3034] while ultrasound-guided VABs have much lower rates of underestimation (0–22 %) [33, 35]. Grady et al found no underestimation in lesions completely removed by 8 G ultrasound-guided VAB [35].…”
Section: Resultsmentioning
confidence: 99%
“…The highest underestimation rates (22–65 %) are published for ultrasound-guided 14G CNB [21, 22, 25, 3034] while ultrasound-guided VABs have much lower rates of underestimation (0–22 %) [33, 35]. Grady et al found no underestimation in lesions completely removed by 8 G ultrasound-guided VAB [35]. For MRI-guided VAB only two studies exist regarding underestimation of ADH showing underestimation rates of 32 and 38 %, respectively [36, 37].…”
Section: Resultsmentioning
confidence: 99%
“…This finding was in agreement with the existing data, lending additional support to the idea that MRI characteristics are not predictive of upstaging to malignancy. [6][7][8][9][13][14][15] Finally, all upstaged lesions in our study were in patients with a history of breast cancer. Although not statistically significant, this characteristic is likely related to the small sample size and our specific population at a tertiary cancer center.…”
Section: Discussionmentioning
confidence: 99%